INVESTIGATION OF AGEING EFFECTS ON THE ELECTRICAL PROPERTIES OF POLYANILINE / GOLD NANOCOMPOSITES - Afzal, Asma B.; Akhtar, M. J. (The Nucleus, 2011)
PANI/Au nanocomposites, synthesized by incorporation of separately prepared gold nanoparticles in NMP solution of PANI have been aged at accelerated temperature of 120 Â°C to simulate a storage period of 2 years at 25 Â°C. The impedance spectroscopic studies of NMP plasticized aged nanocomposite films suggest microphase separation into reduced and oxidized repeat units. There is crosslinking of the PANI films during ageing thereby hindering the charge transfer between PANI chains and gold nanoparticles, as a result, resistivity is increased.